IDENTIFIKASI SEBARAN MINERAL BIJIH BESI DENGAN MENGGUNAKAN METODE RESISTIVITAS DAN INDUCED POLARIZATION (IP) DI KECAMATAN MUARA UYA, KABUPATEN TABALONG, PROVINSI KALIMANTAN SELATAN - Ferial, Deki; Natalisanto, Adrianus Inu (GEOSAINS KUTAI BASIN, 2019)
The geoelectric method is one of the geophysical methods. It studies the electrical properties on earth and detects on the surface of the earth. In this case includes the measurement of potential, currents and electromagnetic fields that occur either naturally or due to injection of current into the earth. This research was conducted at the mining site of PT. Bakal Makmur Sejahtera (BMS). Geographically, the mining location of PT. BMS is located at 173° 15' 32.8896" BT, 0° 10' 32.5209" LS. In the five line was measured to obtain the values of apparent resistivity (ρa) and apparent chargeability (ma) this using the Wenner-Schlumberger array of 3,900 data. These values are processed by the res2dinv program to obtain 2-D from each line. The results of geoelectric modeling there is an indication of iron ore from lines 1 to 6 with a distribution of resistivity values 43,5 Ω.m to 249 Ω.m and distribution of chargeability values 34,4 msec to 99,7 msec. The interpretation supporting by outcrop data in the field.